AN OPEN LABELLED RANDOMISED CLINICAL TRIAL ON EFFICACY OF HARITAKI MODAKA AND ABHIJEET TAILA IN THE MANAGEMENT OF COMPUTER VISION SYNDROME (International Journal of Ayurveda and Pharma Research, 2020)
Computer Vision Syndrome is the new nomenclature to the visual, ocular, and systemic symptoms arising due to the long time and improper working on the computer. Computer Vision Syndrome is a repetitive strain disorder as defined by the American Optometric. With progressive increase in the usage of computers, the term Repeated Stress Injury has found a place in contemporary medical science. The ocular complaints experienced by computer users typically include eyestrain, eye fatigue, burning sensations, irritation, redness, blurred vision, and dry eyes, among others. This group of symptoms is called Asthenopia. The incidence of Computer Vision Syndrome is as high as 50% to 90% among the employees of computer occupation. The causes for the inefficiencies and the visual symptoms are a combination of individual visual problems and poor office ergonomics. Material & Methods: In this clinical study on CVS, 60 patients were registered from Shalakya tantra OPD, and all of them completed the treatment. In Group A, 30 patients were prescribed Abhijeet Taila for Pratimarsha Nasya and in Group B, 30 patients were prescribed Haritaki Modak tablets internally and Abhijeet Taila for Pratimarsha Nasya. Results: In total, 20% and 33.33% patients got completely cured in Group A and B respectively. Discussion: Both the drugs were effective in managing the condition, but it was observed they were more effective when given together. Multi-centric studies with larger sample size on the same drugs should be carried out to evaluate the effect of the drugs and, also so that the observations can be noted well and can be better suggested.